2006
DOI: 10.1016/j.taap.2006.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific induction of cytochrome P450s in nonylphenol-treated FVB/NJ mice

Abstract: Nonylphenol (NP) is a breakdown product of nonylphenol ethoxylates, which are used in a variety of industrial, agricultural, household cleaning, and beauty products. NP is one of the most commonly found toxicants in the United States and Europe and is considered a toxicant of concern because of its long half-life. NP is an environmental estrogen that also activates the pregnane X-receptor (PXR) and in turn induces P450s. No study to date has examined the gender-specific effects of NP on hepatic P450 expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 58 publications
4
60
2
1
Order By: Relevance
“…As shown in Figure 7, PF9601N significantly inhibited the formation of 6β-hydroxytestosterone, marker of CYP3A activity, by about 78% as compared to control values. Furthermore the 30% inhibition of 15β-hydroxytestosterone formation, catalysed by CYP3A confirmed the previous data (28). The inhibition study performed on human liver microsomes showed that, as observed in mouse liver microsomal preparations, only ketoconazole significantly inhibited by about 30% PF9601N Ndealkylation rate (Figure 8).…”
Section: Inhibition Of Pf9601n Metabolism By Mice and Human Liver Micsupporting
confidence: 88%
“…As shown in Figure 7, PF9601N significantly inhibited the formation of 6β-hydroxytestosterone, marker of CYP3A activity, by about 78% as compared to control values. Furthermore the 30% inhibition of 15β-hydroxytestosterone formation, catalysed by CYP3A confirmed the previous data (28). The inhibition study performed on human liver microsomes showed that, as observed in mouse liver microsomal preparations, only ketoconazole significantly inhibited by about 30% PF9601N Ndealkylation rate (Figure 8).…”
Section: Inhibition Of Pf9601n Metabolism By Mice and Human Liver Micsupporting
confidence: 88%
“…This is not in accordance with the documented in other animals (Zou et al, 2007;Hernandez et al, 2006). The underlying mechanism of genderspecific pharmacokinetics has been related to molecular and physiological factors (Meibohm et al, 2002).…”
Section: Discussioncontrasting
confidence: 55%
“…The amount of CYP450 in female rats is 10%-30% lower than that in male rats (Zou et al, 2007). Hernandez (2006) examined the gender-specific effects of nonylphenol on hepatic CYP450 expression and found that in female mice nonylphenol induced CYP2d10 and CYP 2d13 and down-regulated female-specific p450s, CYP 3a41, and CYP 3a44, whereas male mice treated with nonylphenol showed increased expression of CYP 2a4, CYP 2b9, and CYP 2b10. It is inferred that the different result in our study may due to the lack of genderspecific effects of OTC on hepatic CYP450 expression.…”
Section: Discussionmentioning
confidence: 99%
“…27) Therefore, we examined whether nuclear CAR levels increased by the gastrectomy. Hepatic nuclear fractions were prepared, and CAR protein expression levels were examined by Western blot to determine the level of nuclear The mice of the sham operation group (white) and the gastrectomy group (black) were allowed free access to the diet.…”
Section: )mentioning
confidence: 99%
“…Therefore, when the expression of CYP3A11 is regulated by CAR, the expression of not only CYP3A11 but also CYP2B10 is expected to increase. The expression of CYP2B10 was also examined 27) (Fig. 5).…”
Section: )mentioning
confidence: 99%